2012
DOI: 10.1021/ja3041338
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Selective α,β-Deuteration of Bioactive Amines

Abstract: A novel and convenient protocol for the catalytic hydrogen-deuterium exchange of biologically active tertiary amines utilizing the borrowing hydrogen methodology has been developed. In the presence of the readily available Shvo catalyst, excellent chemoselectivity toward α- and β-protons with respect to the nitrogen atom as well as high degree of deuterium incorporation and functional group tolerance is achieved. This allowed for the deuteration of complex pharmaceutically interesting substrates, including exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(86 citation statements)
references
References 66 publications
0
84
0
2
Order By: Relevance
“…The decay of the concentration with time was similar for the two substrates (5a and 5a-d 2 ) ( Figure S9 in the Supporting Information), and the calculated KIE was 1.24 ± 0.35. 25 This low KIE value suggests that the alcohol oxidation step is not the rds of the reaction. 26,27 During the reduction of 8 by the iridium−hydride, an Ir−H bond is broken.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The decay of the concentration with time was similar for the two substrates (5a and 5a-d 2 ) ( Figure S9 in the Supporting Information), and the calculated KIE was 1.24 ± 0.35. 25 This low KIE value suggests that the alcohol oxidation step is not the rds of the reaction. 26,27 During the reduction of 8 by the iridium−hydride, an Ir−H bond is broken.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, during dealkylation of tertiary amines, Murahashi demonstrated that the use of water and acid led to the corresponding secondary amine and aldehyde arising from a dehydrogenative hydrolysis in which water acts as a formal oxidant 8c. Several groups judiciously took advantage of these generated iminium/enamine intermediates in the presence of homogeneous catalysts to perform α‐functionalization of tertiary cyclic amines,9 α,β‐deuteration of amines,10 including some enantioselective approaches 11. Well‐defined ruthenium complexes enabled lactam formation from secondary amines and water 12.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclopentadienon-Eisenhydridkomplexe wie Fe1-H 2 (Schema 1) sind seit einem halben Jahrhundert bekannt, lange vor dem Shvo-Präkatalysator. [8] Des Weiteren nutzten Bäckvall und Mitarbeiter die redoxneutralen Eigenschaften dieses Präkatalysators, um ihn in Kombination mit Enzymen für die dynamische kinetische Racematspaltung von Alkoholen und Aminen zu verwenden. In den letzten Jahren kam es aufgrund ihrer einzigartigen katalytischen Eigenschaften, dem einfachen Zugang und ihrer hohen Stabilität zu einem explosionsartigen Anstieg von Anwendungen dieser Komplexe.…”
Section: Introductionunclassified